An illness-focused interactive booklet to optimise management and medication for childhood fever and infections in out-of-hours primary care: study protocol for a cluster randomised trial. Issue 1 (December 2016) - de Bont, Eefje; Dinant, Geert-Jan; Elshout, Gijs; van Well, Gijs; Francis, Nick; Winkens, Bjorn; Cals, Jochen
Abstract Background Fever is the most common reason for a child to be taken to a general practitioner (GP), especially during out-of-hours care. It is mostly caused by self-limiting infections. However, antibiotic prescription rates remain high, especially during out-of-hours care. Anxiety and lack of knowledge among parents, and perceived pressure to prescribe antibiotics amongst GPs, are important determinants of excessive antibiotic prescriptions. An illness-focused interactive booklet has the potential to improve this by providing parents with information about fever self-management strategies. The aim of this study is to develop and determine the effectiveness of an interactive booklet on management of children presenting with fever at Dutch GP out-of-hours cooperatives. Methods/design We are conducting a cluster randomised controlled trial (RCT) with 20 GP out-of-hours cooperatives randomised to 1 of 2 arms: GP access to the illness-focused interactive booklet or care as usual. GPs working at intervention sites will have access to the booklet, which was developed in a multistage process. It consists of a traffic light system for parents on how to respond to fever-related symptoms, as well as information on natural course of infections, benefits and harms of (antibiotic) medications, self-management strategies and 'safety net' instructions. Children < 12 years of age with parent-reported or physician-measured fever are eligible for inclusion. The primary outcome is antibiotic prescribing during the initial consultation. Secondary outcomes are (intention to) (re)consult, antibiotic prescriptions during re-consultations, referrals, parental satisfaction and reassurance. In 6 months, 20, 000 children will be recruited to find a difference in antibiotic prescribing rates of 25% in the control group and 19% in the intervention group. Statistical analysis will be performed using descriptive statistics and by fitting two-level (GP out-of-hours cooperative and patient) random intercept logistic regression models. Discussion This will be the first and largest cluster RCT evaluating the effectiveness of an illness-focused interactive booklet during GP out-of-hours consultations with febrile children receiving antibiotic prescriptions. It is hypothesised that use of the booklet will result in a reduced number of antibiotic prescriptions, improved parental satisfaction and reduced intention to re-consult. Trial registration ClinicalTrials.gov identifier:NCT02594553 . Registered on 26 Oct 2015​, last updated 15 Sept 2016.